Crystallization Behaviour of Vitreous Coal Fly Ash - Biljana Angjusheva, Emilija Fidancevski (My University, 2021)
Glass-ceramics were produced by controlling crystallization of glass, obtained by quenching of coal fly ash. Crystallization behaviour of vitreous fly ash was followed by determination of characteristic temperatures. Glass transition temperature (Tg) and peak temperature (Tp) of parent glass were 480 oC and 1040 oC, respectively. It was confirmed that the intense crystallization process occurs at the temperature region between 900 oC and 1050 oC. Based on the ratio Tg/Tm it was found that the crystallization mechanism for parent glass is of a bulk type (0.41). Glass-ceramics were obtained by the consolidation of parent glass and exposure on defined thermal treatments. XRD studies show that the ratio of crystalline and amorphous phases in glass-ceramics sintered at 1050 o/60 min was 68/32, with the major crystalline phase of calcium aluminum silicate (anorthite). SEM and EDS analysis shows that crystaline phases are homogeneously dispersed in the glassy matrix. Glass-ceramics could be potentially used as construction material.
Keywords: crystallization, coal fly ash, glass, quenching, glass-ceramics